Penerapan Supply Chain Management di PT Nippon Indosari Corpindo Tbk - Kolompo, Septian Aditya (Fakultas Ekonomi Universitas KristenTentena, 2024)
This research discusses the application of Supply Chain Management (SCM) at PT Nippon Indosari Corpindo Tbk., one of the leading companies in the bakery industry in Indonesia. Focusing on enhancing operational efficiency and reducing production costs, this study explores how PT Nippon Indosari Corpindo Tbk. integrates advanced technology and Supply Chain Management strategies to maintain product quality while minimizing losses. Through the use of the Just In Time (JIT) concept, Advanced Planning & Optimization (APO) tool, and Radio Frequency Identification (RFID), the company has successfully improved inventory management, expedited distribution, and maximized customer satisfaction. The research findings show that effective SCM implementation has reduced the bullwhip effect, increased transparency in the flow of raw materials and finished products, and supported the sustainability of the company's operations. Thus, this study provides important insights into the benefits of SCM in the food and beverage industry, especially for companies operating on a large scale with dynamic market demands